Islamic Prophetic Counseling: An Intervention Strategy in Developing Students' Noble Character - Santosa, Hardi; Annafiri, Ahmad Zaki; Inawati, Iin; Prasetya, Akhmad Fajar; Sahrir, Muhammad Sabri bin (Buletin Konseling Inovatif, 2025)
This study aims to test the effectiveness of Islamic prophetic counseling in developing students' noble morals. The research method uses a true experiment involving a control group. The selection of the control group uses the waiting-list control group model, with consideration of the ethical aspects of the study. The research sample involved 244 students captured the profile of noble morals and their spiritual activism. While the hypothesis test involved 50 students who were divided into control and experimental groups. The sample selection was carried out randomly with the random assignment technique. The research data were collected using a noble moral questionnaire. The covariate analysis test was used to analyze the data obtained. The results of the hypothesis test showed a significance value of 0.002, smaller than the research alpha (α) value of 0.05. Islamic prophetic counseling has been proven effective in developing noble morals. Based on empirical evidence, this study makes a new contribution by strengthening the role of spiritual counseling as the fifth force in a comprehensive counseling and psychotherapy paradigm.